Successful prevention of secondary burn progression using infliximab hydrogel: A murine model. Issue 4 (June 2022) - White-Dzuro, Colin G.; Burns, Brady; Pollins, Alonda; Rector, John A.; Assi, Patrick E.; Thomas, Harrison C.; Jackson, Kianna; Perdikis, Galen; Al Kassis, Salam; Bellan, Leon M.; Thayer, Wesley P.
Highlights: Early conversion of partial to full thickness burns is a major cause of morbidity. The pathogenesis is not well understood, but immune response thought to play a role. Anti-TNF-α antibody immunotherapy prevents burn conversion in a murine model. Previous work implicated eosinophils, but shown here to not be a major factor. Future studies will look at other inflammatory mediators including macrophages. Abstract: Introduction: Burn injury remains a serious cause of morbidity and mortality worldwide. Severity of burns is determined by the percentage of burned area compared to the body surface area, age of patient, and by the depth of skin and soft tissue involvement; these factors determine management as well as prospective outcomes. The pathophysiology of partial- to full-thickness burn conversion remains poorly understood and is associated with a worse overall prognosis. Recent studies have demonstrated that an altered inflammatory response may play a significant role in this conversion and therefore a reduction in early inflammation is crucial to ultimately decreasing burn severity and morbidity. We hypothesize that the application of a microcapillary gelatin–alginate hydrogel loaded with anti-TNF-α (infliximab) monoclonal antibodies to a partial-thickness burn will reduce inflammation within partially burned skin and prevent further progression to a full-thickness burn. Methods: Assembly of the microfluidic hydrogels is achieved by embedding microfibers within a hydrogel scaffold composed of a gelatin–alginate blend, which is then soaked in a solution containing anti-TNF-α antibodies for drug loading. 12 young (2–4 months) and 12 old (>16 months) mice were given partial thickness burns. The treatment cohort received the anti-TNF-α infused hydrogel with an occlusive dressing and the control cohort only received an occlusive dressing. Mice were euthanized at post-burn day 3 and skin samples were taken. Burn depth was evaluated using Vimentin immunostaining. Results: All mice in the treatment cohort demonstrated decreased conversion of burn from partial to full thickness injury (old = p < 0.01, young = p < 0.001) as compared to the control group. Old mice had greater depth of burn than young mice (p < 0.001). There were greater eosinophils in the treatment cohort for both young and old mice, but it did not reach statistical significance. Conclusion: The application of a novel microcapillary gelatin–alginate hydrogel infused with anti-TNF-α antibody to partial thickness burns in mice showed reduction in partial to full thickness burn secondary progression as compared to controls using this murine model; this promising finding might help decrease the high morbidity and mortality associated with burn injuries.